Ionic liquids for the separation of benzene and cyclohexane – COSMO-RS screening and experimental validation - Salleh, M. Zulhaziman M.; Hadj-Kali, Mohamed K.; Hashim, Mohd Ali; Mulyono, Sarwono (Elsevier, 2018)
The separation of benzene and cyclohexane from their mixture is difficult to perform via conventional distillation because of their close boiling points. In this work, liquid-liquid extraction using ionic liquids (ILs) is suggested for this purpose and 16 cations and 13 anions were selected to form 208 possible ILs screened with the Conductor-like Screening Model for Real Solvents (COSMO-RS) module. The screening result was experimentally validated by liquid–liquid extraction using four of the top ranked ILs, namely 1-ethyl-3-methylimidazolium acetate ([C2mim][Ac]), 1-ethyl-3-methylimidazolium dicyanamide ([C2mim][N(CN)2]), 1-ethyl-3-methylimidazolium thiocyanate ([C2mim][SCN]) and 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([C2mim][Tf2N]). The ternary liquid–liquid equilibria for these ILs with benzene and cyclohexane were investigated at 25 °C and 1 atm with feed concentration of benzene ranging from 10 to 60 wt%. Good agreement was achieved between the tie-lines obtained from the COSMO-RS model and those obtained experimentally. The performance of ILs used in this study was compared with organic solvents, other ILs, and deep eutectic solvents reported in literature. The results of selectivity and distribution ratio confirmed that COSMO-RS was a reliable method for solvent screening and demonstrated the suitability of the selected ILs as extracting solvents. In all ternary systems, no IL was detected in the cyclohexane layer and the concentration of cyclohexane in the IL layer was very low. This observation indicated that there was minimum cross-contamination between the phases and therefore less energy will be required for the solvent recovery.